Understanding stakeholders' perception on integrating ICT in teaching and learning science subjects: Experiences from Tanzanian secondary schools - Abdallah Ngodu; Placidius M. Ndibalema; Francis William (Academy of Cognitive and Natural Sciences, 2024)
This study investigated stakeholders' perceptions of the integration of ICT in teaching and learning science subjects in secondary schools. A cross-sectional survey design, using a mixed approach, guided the study. Survey questionnaires and interviews were used for data collection. A total of 221 respondents, including students, teachers, heads of schools and district education officers, were sampled. The SPSS version 24 was used for quantitative data analysis. The qualitative data from the interviews were subjected to thematic analysis. Results indicate that stakeholders had positive perceptions of the benefits of integrating ICT in teaching science subjects. However, their positive perception was hampered by the accessibility of ICT materials, insufficient pedagogical knowledge and limited support from school management. Therefore, it affects the integration of ICT in teaching and learning science subjects. The study recommends government and management support to ensure sufficient ICT materials. Further, teachers should be equipped with sufficient pedagogical knowledge for ICT integration in teaching and learning science subjects.